2010
DOI: 10.1093/esr/jcq028
|View full text |Cite
|
Sign up to set email alerts
|

Pooling of Economic Resources: A Comparison of Norwegian Married and Cohabiting Couples

Abstract: Using Norwegian survey data (n = 4116), we study couples" likelihood of pooling their economic resources. The proportion of cohabitation compared to marriages is high in Norway. Over the last decades, tax policy and the social security system have moved towards equating cohabitation with marriage. Our knowledge of the economic organization of the two types of couples is, however, rather imperfect. Our main hypothesis is that cohabitants are less likely to pool their economic resources than married couples, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 28 publications
12
95
0
2
Order By: Relevance
“…Vogler (2005) reports about a study conducted by Ludwig-Mayerhofer (2000) who found that about 70% of married couples in Germany use the non-segregated joint pooling system to manage their money, whereas cohabiting couples mainly manage their money separately. Similar patterns are found for Norway, Sweden and Canada (Vogler, 2005;Lyngstad et al, 2010). However, most cohabiting couples who have at least one biological child together pool incomes, similar to married couples (McRae, 1993;Winkler, 1997;Lewis, 2001).…”
Section: Income Poolingmentioning
confidence: 56%
See 2 more Smart Citations
“…Vogler (2005) reports about a study conducted by Ludwig-Mayerhofer (2000) who found that about 70% of married couples in Germany use the non-segregated joint pooling system to manage their money, whereas cohabiting couples mainly manage their money separately. Similar patterns are found for Norway, Sweden and Canada (Vogler, 2005;Lyngstad et al, 2010). However, most cohabiting couples who have at least one biological child together pool incomes, similar to married couples (McRae, 1993;Winkler, 1997;Lewis, 2001).…”
Section: Income Poolingmentioning
confidence: 56%
“…Phipps and Burton, 1995). The increasing plurality of family structures raises doubts that the assumptions of pooling and equal sharing of incomes remain valid, because prior evidence suggests that the majority of cohabiting couples maintain systems of individualized management of resources instead of pooling each partner's whole income (Vogler, 2005;Kenney, 2006;Lyngstad et al, 2010). Implications based on assumptions of the pooling and equal sharing of incomes therefore remain valid for a declining number of households, if at all.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cohabiting partners may have a lower propensity to have children together and to develop relationships with the other partner"s relatives (Hogerbrugge and Dykstra 2009). Couples in informal unions may avoid pooling resources, holding jointly owned property, and adopting a division of responsibilities within and outside of the household in which one of the partners is economically dependent on the other (Lyngstad, Noack, and Tufte 2011). Being in an informal union may also encourage the partners to develop their own skills and interests, rather than sacrificing them for the sake of the joint household.…”
Section: Literature Overview: Freedom In Cohabitationmentioning
confidence: 99%
“…This extensive literature has made great strides towards understanding the trends (e.g., Perelli-Harris and Lyons-Amos 2015; Hoem et al 2009;Heuveline and Timberlake 2004;Andersson and Philipov 2002;Kiernan 2004), correlates (e.g. Hiekel, Liefbroer, and Poortman 2014;Perelli-Harris et al 2010;Wiik, Keizer, and Lappegård 2012), and effects of partnership formation (e.g., Hiekel and Castro-Martin 2014;Lyngstad et al 2011;Soons, Liefbroer, Kalmijn 2009). However, most of these studies are primarily the outcome of a structured process of data collection in which respondents fit their answers to predefined alternatives.…”
Section: Introductionmentioning
confidence: 99%